Implementación de un sistema Experto para el diagnóstico de desnutrición en niños menores de 5 años utilizando lógica fuzzy - Gutiérrez Lozano, Fernando (2015)
This thesis presents a model of expert system through the application of artificial intelligence techniques, which captures the basic knowledge that enables a person to act as an expert face complicated problems, in this case the expert system will take care diagnosed by Fuzzy Logic degree of malnutrition patient._x000D_ Expert System with the following characteristics is designed: the symptoms and signs of patients considered as input variables, one Base of Acts that stores individual patient's symptoms, a Knowledge Base represented by production rules formalized by predicate logic containing all the knowledge of human expert, an inference engine that uses tree search and / Or and finally the output variables._x000D_ Subsequently expert system simulation is performed by a prototype developed in the Eclipse IDE, likewise, is designed knowledge base with the help of the library "jFuzzyLogic" that will verify the results and compare with the actual results. From the results obtained in tests the expert system and concluded that the diagnosis obtained have a degree of reliability that is accepted by the human expert is evaluated